Compatibility of Trypsin-Modified Human Erythrocytes in the Rubella Hemagglutination-Inhibition Test Employing Three Serum Treatment Procedures - Nelson, Donald B. (1974)
Results of comparative tests using trypsin-modified human type O erythrocytes and cells from newly hatched chickens with three standard serum treatment methods for rubella hemagglutination-inhibition techniques are reported. The kaolin, heparin-manganous chloride and dextran sulfate-calcium chloride methods could all be used with both cell types. Reproducibility with heparin-manganous chloride and dextran sulfate-calcium chloride was excellent with both cell types. Both methods gave generally higher antibody titers than the kaolin procedure. However, the use of human cells resulted in a more sensitive system than chicken cells with all serum treatment methods.